Farmer’s Awareness on Effective Delivery of Farm Information through ICT Mediated Extension Service in Bangladesh - Moon, Sadia Jahan; Miah, M. Abdul Momen; Berg, Trygve (European Scientific Journal, ESJ, 2016)
The main focus of the study was to find out the level of awareness about effective delivery of farm information to the farmers through ICT mediated extension service in Bangladesh. The factors influencing awareness of the farmers and the problems faced by the farmers in getting farm information were also explored. Data were collected from a sample of 100 farmers out of 700. A structured interview schedule and check list were used in collection of data through face to face interviewing and focus group discussion (FGD) during October to November in 2012. The awareness was measured by using a 3 point rating scale and appropriate weights were assigned to each of the responses. By adding the weights of responses awareness score was calculated. The effectiveness of ICT mediated extension services was considered based on amount of information being supplied, acceptability, diversity, demand driven and outcome in using information by the farmers. About two-thirds (68 percent) of the farmers had moderate awareness while almost one fourth (26 percent) having high and only 6 percent had low awareness about effective delivery of farm information by ICT centers. The level of education, farm size, family size, annual income, training exposure, organizational participation and extension media contact of the farmers were significantly correlated with their awareness. The stepwise multiple regression analysis showed that out of 9, four variables such as organizational participation, annual income, farm size and family size of the farmers combinedly explain 50 percent variance regarding awareness of effective delivery of farm information. Rendering inadequate services of field extension agents, frequent power disruption, lack of skilled manpower (extension agents) at ICT centers, lack of training facilities for the farmers, and poor supervision and monitoring of field extension activities were the major problems as mentioned by the farmers for effective dissemination of farm information.